Progress in Automation, Robotics and Measuring Techniques Volume 2 Robotics - Szewczyk, Roman; Zieliński, Cezary; Kaliczyńska, Małgorzata (Advances in Intelligent Systems and Computing, 2015)
This book presents recent progresses in control, automation, robotics, and measuring techniques. It includes contributions of top experts in the fields, focused on both theory and industrial practice. The particular chapters present a deep analysis of a specific technical problem which is in general followed by a numerical analysis and simulation, and results of an implementation for the solution of a real world problem. The presented theoretical results, practical solutions and guidelines will be useful for both researchers working in the area of engineering sciences and for practitioners solving industrial problems.    .